A Critical Appraisal of absenteeism in an Organisation (A Case Study of Sriram Pistons and Rings Ltd., Meerut) - Yadav, Pratibha Rani (Journal of Commerce and Trade, 2017)
Workers who are away from work on recognized holidays, vacations, approved leaves of absence or leaves of absence allowed for under the collective agreement provisions would not be included in absenteeism. It is unauthorized, unexplained, avoidable and willful absence from work. Absence can also be defined as- “The temporary cassation of work for not less than one whole working day, on the initiative of the worker when his presence is expected”. Thus, an employee who reports for duty even for a past of the day or shift is not treated as an absence. Many absenteeism strategies ignore the impact of illness and disease on the workplace and its major role in determining work attendance. Therefore, it has been supposed to take an inner view of the real position of the Absenteeism, the need of the workers and the effects on the company. So, this study is proposed to know the role of absenteeism and their effective stage wise eradication. The location of the proposed study is Sriram Pistons and Rings Ltd., Meerut. The workers serving in production process in the company constitute the universe of the study. The research design of the proposed study is exploratory in nature and data is collected by administering a questionnaire to the selected respondents. The questionnaire is pre tested before administering it to the selected respondents. All the selected workers are personally interviewed to have first hand information.